Global regional and national burden of intracerebral hemorrhage between 1990 and 2021 - Zhao-wei Wang; Mei-ping Wan; Jia-hui Tai; Yong Wang; Min-yi Yin (Scientific Reports)
Abstract Intracerebral hemorrhage (ICH) represents one of the most devastating forms of stroke, characterized by spontaneous bleeding into the brain parenchyma. This neurological emergency carries a substantial burden of mortality and long-term disability worldwide. A comprehensive understanding of ICH’s evolving global impact from 1990 to 2021 remains essential for healthcare planning and resource allocation. We conducted a systematic analysis of ICH burden utilizing data from the Global Burden of Disease (GBD) Study 2021. Key epidemiological indicators were extracted, including prevalence, incidence, mortality, and disability-adjusted life-years (DALYs). Temporal trends were quantified through estimated annual percentage changes (EAPCs) in age-standardized rates of prevalence (ASPR), incidence (ASIR), mortality (ASDR), and DALYs across the study period. The association between disease burden and socioeconomic development was examined using the sociodemographic index (SDI) as a metric of societal development. This analytical framework enabled assessment of ICH burden across global, regional, and national scales while accounting for demographic and socioeconomic variations. From 1990 to 2021, while absolute ICH cases increased globally, age-standardized incidence rates declined. Our novel geographic analysis revealed East Asia bearing the highest burden, with Eastern Europe showing the highest age-standardized rates. Gender analysis identified distinct age-specific patterns, with males above 35 showing higher risk, particularly in Eastern Europe, while South Asia demonstrated minimal gender differences. Our innovative analysis during COVID-19 revealed healthcare system strength significantly impacted ICH outcomes, with well-resourced countries maintaining better outcomes. Regional risk factor assessment showed varying impacts of high systolic blood pressure across regions, highest in Southern Sub-Saharan Africa and lowest in Oceania. Future projections through 2030 indicate improving survival rates in most regions, except in low-income areas, highlighting persistent healthcare disparities. While the absolute number of ICH cases, deaths, and DALYs increased globally from 1990 to 2021, age-standardized rates showed a decreasing trend. This suggests improvements in prevention and management strategies over time. However, the burden of ICH remains substantial and unevenly distributed across regions, with lower SDI areas facing a disproportionately higher burden. These findings highlight the need for targeted interventions and resource allocation, particularly in regions with higher ICH burden, to further reduce the global impact of this devastating condition.